Men Against Violence: Engaging men and boys in prevention of family violence. (21st April 2020) - Ringin, Luke; Robinson, Margie; Greville, Heath; Papertalk, Lennelle; Thompson, Sandra
Abstract: Issues addressed: Discussion of family violence is important but many men and boys struggle to engage with the topic. Primary prevention approaches focus on communicating with and educating the population, including men and boys, in the areas of healthy relationships, gender and violence. There can be both barriers to and also gains from these interventions. This paper describes a project implemented in Geraldton, Western Australia, and discusses what has been effective and ineffective during the project. Methods: The 'Men Against Violence' project targeted men and boys through local sporting clubs in the City of Greater Geraldton, in the Midwest region of Western Australia, through the use of face to face education, community radio and television interviews and other appropriate engagement strategies. 'Men Against Violence' events were held to connect with local male community members and address the role men can have in family violence prevention. Results: We describe the three key engagement activities, working with the local Australian Rules football league, state‐league basketball team and a local high school Aboriginal football academy. These strategies provided avenues for contact with and the education of men and boys aged 12 years and older. Conclusion: Through successful partnerships with a number of local organisations, the 'Men Against Violence' project saw a high level of engagement with local men. The project also gained strong community support, with pockets of resistance encountered and managed. So what: The 'Men Against Violence' project experienced highlights and barriers throughout the pilot project that can guide and inform future family violence prevention programs.